Effectiveness of Non-Pharmacological Methods, Such as Breastfeeding, to Mitigate Pain in NICU Infants - Zoi Koukou; Anatoli Theodoridou; Eleftheria Taousani; Angeliki Antonakou; Eleftherios Panteris; Styliani-Stella Papadopoulou; Anna Skordou; Stavros Sifakis (MDPI AG, 2022)
Neonates do experience pain and its management is necessary in order to prevent long-term, as well as, short-term effects. The most common source of pain in the neonatal intensive care unit (NICU) is caused by medically invasive procedures. NICU patients have to endure trauma, medical adhesive related skin injuries, heel lance, venipuncture and intramuscular injection as well as nasogastric catheterization besides surgery. A cornerstone in pain assessment is the use of scales such as COMFORT, PIPP-R, NIPS and N-PASS. This narrative review provides an up to date account of neonate pain management used in NICUs worldwide focusing on non-pharmacological methods. Non-steroidal anti-inflammatory drugs have well established adverse side effects and opioids are addictive thus pharmacological methods should be avoided if possible at least for mild pain management. Non-pharmacological interventions, particularly breastfeeding and non-nutritive sucking as primary strategies for pain management in neonates are useful strategies to consider. The best non-pharmacological methods are breastfeeding followed by non-nutritive sucking coupled with sucrose sucking. Regrettably most parents used only physical methods and should be trained and involved for best results. Further research in NICU is essential as the developmental knowledge changes and neonate physiology is further uncovered together with its connection to pain.